Conquering fear and embracing joy in shaping marketing strategy - Caesarina, Aldila; Alfina, Alfina; Narendra Wardhana, Aditya; Risfana Sari, Lisa (Journal of Innovation in Business and Economics, 2023)
This research investigates the complex relationship between Problematic Internet Use (PIU) and various psychological aspects, including Psychology and Mental Health (PMH), Fear of Missing Out (FOMO), and Social Media Fatigue (SMF). Furthermore, this study was designed to test various psychological conditions regarding the Desire to Disconnect (DD), which ultimately results in the Joy of Missing Out (JOMO). Through a structural equation model involving 310 college student respondents, this study found that PIU is associated with suffering in PMH, heightened FOMO, increased SMF, and that FOMO exacerbates SMF. Moreover, SMF drives DD, and ultimately, DD causes JOMO. In response to these findings, we argue that achieving a balance in marketing between FOMO-based online strategies and JOMO-based offline strategies needs to be a priority for sustainable brand marketing. Additionally, it is crucial to consider ethical issues in content moderation aligned with FOMO to safeguard consumers' psychological well-being.